Biotransformação de terpenos naturais por fungos de solos e aproximação a biossintese de sesquiterpenos isolados do fungo fitopatôgeno Botrytis cinerea - Gabriel Franco dos Santos (2017)
Biotransformation of natural terpenes by soil fungi and approach to the biosynthesis of sesquiterpenes isolated from the phytopathogenic fungus Botrytis cinerea. In this work, we sought to obtain new trachylobanic acid derivatives by biotransformation with Aspergillus tubingensis, Fusarium proliferatum, Mucor plumbeus, Paecilomyces lilacinus, Penicillium minioluteum and Syncephalastrum racemosum, in order to find new derivatives exhibiting greater inhibitory activity of acetylcholinesterase (AChE), enzyme related to Alzheimer's disease, than the substrate used. From the biotransformation of trachylobanic acid by Mucor plumbeus were isolated two products of biotransformation, among which one is not reported in the literature. When It was used Syncephalastrum racemosum as biotransformation agent, we isolated three products, being two of them unpublished. Ali products of bitransformation showed inhibition activities greater than the trachylobanic acid. In addition, we realized studies of secondary metabolism of null mutant of the fungus Botrytis cinerea ([delta]bcabal-4 and [delta]bcbot4), in order to investigate which biosynthetic routes are involved in the production of abscisic acid, and what cryptic metabolites are produced by the mutant [delta]bcbot4. Through the study of null mutants [delta]bcabal-4 of B. cinerea, it was possible to identify two biosynthetic intermediaries, from Abcabal and [delta]bcaba2, respectively. From these intermediaries, it was possible to propose a biosynthetic route for the formation of abscisic acid by fungi. From the study of secondary metabolites of [delta]bcbot4 mutant, we isolated fifteen compounds, of which seven are known, two have not been elucidated and four are reported for the first time in this work.